Validação de metodologia analítica para análise de aflatoxina M1 e sua ocorrência no leite bovino comercializado no sul do Brasil - Oliveira, Maurício Schneider (2010)
Mycotoxins are toxic substances resulting from the secondary metabolism of different strains of fungi. Among the known mycotoxins, aflatoxins are considered the most important, due to its presence and magnitude of contamination in food intended for human consumption and animal. From the observation that milk-producing animals that consume feed contaminated with aflatoxin B1 aflatoxin M1 will excrete in their milk, it is necessary to develop mechanisms for accurate and reliable analysis of this contaminant. Milk is one of the most complete foods "naturally" available for man, with a balanced composition of nutrients; their consumption is recommended for all stages of human development, especially in the early stages of life. This work validated a methodology for analysis of aflatoxin M1 in fluid milk and milk powder, based on the extraction and purification with immunoaffinity column with subsequent separation and detection by liquid chromatography coupled to high performance tandem mass spectrometry. The limits of detection and quantification were determined 0.003 and 0.007 μg L-1 for fluid milk and 0.003 and 0.125 μg L-1 for milk powder. The coefficients of global recovery for the method of extraction of aflatoxin M1 were 95.2% for fluid milk and 95.9% for milk powder, with a standard deviation of 5.7% and 5.3% respectively. Following the development and validation of the analytical method was a study of the occurrence of aflatoxin M1 in milk samples and fluid samples of milk powder. At a total, 173 samples were analyzed, being 123 of them for fluid milk, divided into: 23 raw milk samples, 21 samples of pasteurized milk, and 79 samples of milk UHT; obtained from outlets in the three states of southern Brazil. For milk powder were analyzed 50 samples obtained from retailers in the state of Rio Grande do Sul. The results showed an incidence of positivity of 90.2% (111) in samples of fluid milk in concentration levels from 0.01 - 0.60 μg L-1 with an average contamination of 0.07 μg L-1. For samples of milk powder, 100% (50) were contaminated at levels of concentration from 0.06 - 1.58 μg L-1 with average contamination of 0.54 μg L-1. For samples of liquid milk, 46% (57) exceeded the maximum permitted levels of aflatoxin M1 in milk, proposed by the European Union legislation (0.05 μg L-1) and 0.8% (1) exceeded the proposed maximum permitted by Brazilian legislation (0.5 μg L-1). For the samples of milk powder, 98% (49) exceeded the maximum allowed by the proposed European Union legislation. Based on these results, the method was sensitive and suitable for determination of aflatoxin M1 levels proposed by the Brazilian and European legislations. The high occurrence of aflatoxin M1 in the samples suggests that the monitoring of aflatoxin M1 in milk should be a continuous process in our region.